Novel immune-nutritional prognostic ratio predicts long-term survival in stage I–III colorectal cancer - Wang, Kuan; Zhang, Boxiang; Li, Kejin; Zhang, Ziyi; Zeng, Xiangyue; Guan, Jun-Min; Aldridge, Richard; Whitmore, Elizabeth; Pan, Yipeng; Lau, Lucy Yue; Zhao, Zeliang; Chen, Yi (Frontiers in Oncology, 2025)
BackgroundColorectal cancer (CRC) is a common and highly lethal malignancy worldwide. Even after curative resection, patients with stage I–III disease remain at substantial risk of recurrence and mortality. The Prognostic Immune and Nutritional Index (PINI) and lymphocyte-to-monocyte ratio (LMR) have been validated as prognostic markers in cancer, yet their individual predictive performance remains limited. We developed a novel Immune-Nutritional Prognostic Ratio (INPR) integrating PINI and LMR to provide a more comprehensive assessment of immune, nutritional, and inflammatory status. This study further evaluated its value in predicting 1-, 3-, and 5-year survival in stage I–III CRC.MethodsWe retrospectively analyzed data from 556 colorectal cancer patients at two hospitals, with one serving as the validation cohort. Receiver operating characteristic (ROC) curves were used to determine optimal cutoff values for PINI and LMR, and the area under the curve (AUC) was applied to assess predictive performance. KKaplan–Meier analysis showed that lower PINI and LMR were associated with shorter overall survival (OS). The INPR, integrating both markers, demonstrated superior accuracy. Variables linked to OS were selected using the Boruta algorithm and multivariable Cox regression, and a nomogram model was developed and validated internally and externally.ResultsThe Youden index identified optimal cutoff values of 3.50 for PINI and 2.65 for LMR, with low levels independently predicting shorter OS. The INPR, integrating both, stratified patients into low-, intermediate-, and high-risk groups, with 5-year OS rates of 93.30%, 59.35%, and 28.57% in the training cohort (p<0.001). INPR outperformed either marker alone, showing higher AUC. A nomogram incorporating variables selected by the Boruta algorithm and multivariable Cox regression demonstrated stable and superior prognostic performance in both internal and external validation.ConclusionOur findings demonstrate that INPR is a simple, accessible, and effective prognostic tool for postoperative risk stratification in stage I–III CRC patients, providing valuable guidance for optimizing individualized treatment strategies.